Hubungan Kebiasaan Belajar dan Perhatian Orang Tua Terhadap Hasil Belajar Matematika Peserta Didik - Hermawan, Jody Setya; Yolanda, Dhea Rosa; Rapani, Rapani; Astuti, Nelly; Rohman, Fatkhur; Profithasari, Nindy (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The purpose of this study was to determine a significant relationship between study habits and parents' attention to mathematics learning outcomes. This type of research is ex-post facto correlation. The population is 60 students, and is used as a research sample. Questionnaire data collection instrument with a Likert scale. Data analysis uses product moment correlation. It was concluded that the results of the study showed that there was a positive and significant relationship between study habits and parents' attention to mathematics learning outcomes indicated by a correlation coefficient of 0.575 which was at the "strong enough" level with the contribution of variables X1, X2, to Y of 33%. This means that the habit of studying with parents' attention has an effect of 33% on mathematics learning outcomes. Based on the results of research and discussion related to the relationship between study habits and parental attention to students' mathematics learning outcomes. There is a positive and significant relationship between study habits and parents' attention to the mathematics learning outcomes of fifth grade students at Cluster Ki Hajar Dewantara, Seputih Agung District.